Life as a Kiwi at the English Bar - Callaghan, Catherine (Victoria University of Wellington Law Review, 2023)
In honour of Professor Smith's status as a member of the English bar, this article provides an insight into life at the English bar from the perspective of a New Zealander who has practised in England as a barrister for over 20 years. The author describes how the English bar and barristers' chambers operate, and her own path to becoming a King's Counsel, including some of her most memorable cases. The author graduated from Victoria University of Wellington in the mid-1990s with a BA and LLB(Hons), and was awarded the Chapman Tripp Sheffield Young prize for the top law graduate in her year. After completing the LLM at the University of Cambridge (and gaining the highest mark in her year), she worked for two years as a solicitor at Clifford Chance in London before transferring to the bar, where she has practised from Blackstone Chambers ever since. This article is an adaptation of a lecture given at the Victoria University of Wellington Faculty of Law in September 2022.